Insights into microstructural interfaces in aerospace alloys characterised by atom probe tomography - Karen Perkins (Materials Science and Technology, 2016)
Atom probe tomography (APT) is becoming increasingly applied to understand the relationship between the structure and composition of new alloys at the micro- and nanoscale and their physical properties. Here, we use APT datasets from two modern aerospace alloys to highlight the detailed information available from APT analysis, along with potential pitfalls that can affect data interpretation. The interface between two phases in a Ti–6Al–4V alloy is used to illustrate the importance of parameter choice when using proximity histograms or concentration profiles to characterise interfacial chemistry. The higher number density of precipitates and large number of constituent elements in a maraging steel (F1E) present additional challenges such as peak overlaps that vary across the dataset, along with inhomogeneous interface chemistries.